Child trafficking, youth labour mobility and the politics of protection - Howard, Neil (Palgrave Macmillan, 2020)
This book provides the first overarching, empirically grounded, critical analysis of child trafficking as an idea, ordering principle, and artefact of politics. It examines (once) hegemonic anti-child trafficking discourse, policy and practice, and does so by placing secondary literature from around the world in conversation the author's paradigmatic case study of the situation in southern Benin. It deconstructs the child trafficking paradigm, contrasts it with 'real' histories of child and youth labour and mobility, and seeks to explain it by going 'inside' the anti-trafficking field. In doing so, Howard tells a gripping story of ideology at work. Contents: 1. Introduction: Child Trafficking and Its Discontents -- 2. The Dominant Paradigm: Child Trafficking and the Fight Against It -- 3. Challenging the Paradigm: Young People at Work and On the Move -- 4. Explaining the Paradigm: Inside the Anti-Trafficking Field -- 5. Drawing Conclusions.